Long-term and real-life incidence of cancer therapy-related cardiovascular toxicity in patients with breast cancer: a Swedish cohort study - Hubbert, Laila; Mallios, Panagiotis; Karlström, Patric; Papakonstantinou, Andri; Bergh, Jonas; Hedayati, Elham (Frontiers in Oncology, 2023)
Background The administration of anticancer drugs in females with comorbidity increases the risk for cancer therapy-related cardiovascular toxicity (CTR-CVT), which in turn contributes to cardiovascular disease (CVD). Furthermore, a pathophysiological connection between cancer and cardiovascular disease may exist. Objective To assess the long-term risks and predictors of CTR-CVT, including clinical hypertension (HT), coronary artery disease (CAD), heart failure (HF), atrial fibrillation (AF), as well as all-cause mortality in women diagnosed with early breast cancer (BC) and eligible for adjuvant chemotherapy in Sweden. Methods Data were extracted from Swedish registers and medical records on 433 women, 18-60 years of age, diagnosed 1998-2002 with lymph node-positive BC, and considered for adjuvant chemotherapy. CTR-CVT was defined as HT, CAD, HF, or AF after the diagnosis of BC. Follow-up was from the date of BC diagnosis until November 30, 2021, or death. Prevalence of CTR-CVT and all-cause mortality were calculated. Hazard ratios (HR) were determined for factors associated with CTR-CVT. Results The median age was 50 (interquartile range (IQR) 32) years. 910 CTR-CVT events were diagnosed in 311 women with a median of 19.3 (IQR 15,3) years follow-up. The proportions of CTR-CVT events were: HT 281 (64%); CAD 198 (46%); HF 206 (47%); and AF 225 (51%). The cumulative incidence of CTR-CVT was 71.8%, and 50% of all 433 patients developed CTR-CVT within 11.7 years of BC diagnosis (standard deviation (SD) 0.57, 95% confidence interval (CI) 10.6-12.9). Age was a risk factor for CTR-CVT. Anthracycline increased the risk for HF (p=0,001; HR 2,0; 95%CI 1,4-2,8), CAD (p= 0,002; HR 1,7; 95% CI 1,2-2,4), and AF (p=0,013; HR 1,5; 95% CI 1,0-2,0). At the end of the 24-year study period, 227 of the 433 women were alive, and the total cumulative mortality was 47,6%. Conclusions The prevalence of CTR-CVT and all-cause mortality is high after BC diagnosis and treatment, particularly in older patients and those receiving anthracyclines. These findings and the onset of CTR-CVT support cardio-oncology guidelines recommending initial risk stratification and cardiovascular monitoring during treatment, followed by long-term annual screening for cardiovascular risk factors and CTR-CVT among BC survivors.